Uncovering barriers to bilharzia prevention communication in Ugu district, South Africa - Lauren Dyll-Myklebust; Duduzile Zwane (Communicare)
Female Genital Schistosomiasis (FGS), commonly referred to as Female Bilharzia (FB), is a prevalent yet socially obscure disease. Caused by a waterborne parasite, it affects millions of people all over the world. Although it is a global health concern, FB is more pervasive in Sub-Saharan Africa. Motivated by the rapid response to treatment as demonstrated by rural Zimbabwean women, an organisation known as the FB Project conducted research exclusively with this group. Based in KwaZulu-Natal’s Ugu District (Port Shepstone), the FB Project sought to raise an awareness of, to treat and ultimately eradicate the FB threat. This study investigated the most appropriate communication tools for achieving these goals. In 2012, in-depth semistructured interviews were conducted with a sample of 20 female teenagers from both rural and urban areas across the Ugu District. Their perceptions of this issue highlighted various sociocultural, economic and logistical constraints to effective FB communication. This paper explores these barriers and the implications they have for realising the project’s goals. The opinions that are voiced by the participants underscore the value of adopting a participatory communication approach to addressing a health problem. The researcher’s observations are also integrated into the discussion. The responses gathered from the participants were considered as recommendations that could support the design of a contextually-sensitive FB awareness campaign.